Introduction to MongoDB (O'Reilly Media, 2017)
"This video introduces you to MongoDB (a document database) and MongoDB Atlas (MongoDB's database-as-a-service for the cloud). You'll learn how MongoDB differs from other databases, the programming languages it works with, how data is modeled, and how you access MongoDB data. Then you'll explore MongoDB Atlas, its benefits (e.g., how it enables fast time-to-market app deployments), and the tools it provides to view data, perform backups, alerts, and real-time performance metrics. You'll learn how to deploy a cluster, connect to it, and write documents you can manipulate with your own applications."--Resource description page